2015
DOI: 10.1002/elan.201500247
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of Ni and Te‐doped Cobalt Triantimonide in Citrate Solutions

Abstract: Skutterudite compounds form a new class of potential candidates for thermoelectric applications. Cobalt triantimonide (CoSb3) shows good thermoelectric properties at medium and high temperatures. Doping this system with substitution elements, for either Co or Sb or both, may result in an increase of the thermoelectric figure of merit (ZT). This work focused on the electrochemical doping and characterization of films and nanowires of Co‐Sb system in citrate solutions using gold‐coated PCTE templates. The electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…On the surface of a film, it is found that the H 2 bubbles inhibit the electrochemical reaction underneath, blocking the direct contact of the electrode with the electrolyte [24]. Hydrogen evolution during the electrochemical co-deposition of two or more elements at high overpotential results in non-homogenous surface film [20,24,25]. In the NW electrode configuration, Au is found only on the pore wall closed to the surface, i.e., in a small area around the mouth of the nanopore.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the surface of a film, it is found that the H 2 bubbles inhibit the electrochemical reaction underneath, blocking the direct contact of the electrode with the electrolyte [24]. Hydrogen evolution during the electrochemical co-deposition of two or more elements at high overpotential results in non-homogenous surface film [20,24,25]. In the NW electrode configuration, Au is found only on the pore wall closed to the surface, i.e., in a small area around the mouth of the nanopore.…”
Section: Resultsmentioning
confidence: 99%
“…This treatment also greatly increases the reproducibility of the results. The electrochemical treatment of Au in 50 mM H 2 SO 4 and the surface processes that led to a smooth Au surface are detailed elsewhere [20,21].…”
Section: Methodsmentioning
confidence: 99%
“…Anodized Aluminum membrane (AAO). Another template used for nanowires synthesis is the porous aluminum oxide (anodic aluminum oxide, AAO) membrane, which exhibits better stability and chemical inertia compared to PCTE [ 148 ]. AAO templates are obtained using an aluminum foil (99.99%-Merck).…”
Section: Electrochemical Detection and Removal Of Heavy Metalsmentioning
confidence: 99%
“…Various composite nanostructures can be fabricated using electrochemical methods such as template synthesis. It is well-known that electrodeposition in AAO results in nanowire arrays of Fe [ 176 , 177 ], Co [ 166 , 173 , 178 ] and Ni [ 148 , 178 , 179 , 180 ] and their alloys. Composite materials composed of a variety of conductors, insulators, semiconductors and photoconductors were obtained.…”
Section: Electrochemical Detection and Removal Of Heavy Metalsmentioning
confidence: 99%
“…An electrochemical treatment of the Au surface was performed in the beginning of each experiment in order to ensure same surface conditions before the electrodeposition experiment. The electrochemical treatment of Au in 50 mM H2SO4 and the surface processes that led to a smooth Au surface are detailed elsewhere [14].…”
Section: Electrochemical Pre-treatment Of the Electrodementioning
confidence: 99%